Development of predictive finite element models for complete contact fretting fatigue - Maslan, Mohamad Haidir; Sheikh, Mohammad Aslam; Ngatiman, Nor Azazi; Zainal, Nurul Amira; Yahaya, Saifudin Hafiz (Penerbit Akademia Baru, 2025)
Fretting fatigue is complex due to the interactions between contact mechanics and material fatigue properties. Predicting the total life in complete fretting fatigue is challenging due to different types of mechanical assemblies. This research develops a finite element model to predict this life, focusing on fatigue crack initiation and propagation in complete contact fretting fatigue. Crack initiation uses the Smith-Watson-Topper (SWT) criteria, considering wear and the material's elastic-plastic behavior. Crack propagation combines Linear Elastic Fracture Mechanics (LEFM), Elastic-Plastic Fracture Mechanics (EPFM), and Paris' law analysis. The SWT method with the addition of averaging shows good agreement with experimental data for crack initiation, possibly due to high singularities in complete contact. The combined LEFM and EPFM approach also aligns well for crack propagation. The estimated results had a 23% scatter compared to experimental data, demonstrating that combining damage and fracture mechanics provides a robust tool for predicting fretting fatigue life.